Maternal slow-release nitrogen diets during late gestation optimize the energy metabolism in calves’ skeletal muscle - Thaís Correia Costa; Diana Carolina Cediel-Devia; Germán Darío Ramirez-Zamudio; Karolina Batista Nascimento; Mateus Pies Gionbelli; Marcio de Souza Duarte (PLoS ONE, 2026)
The current study aimed to determine the enriched biological process, through proteomic and transcriptome data, associated with maternal slow-release nitrogen diets received during late gestation on the skeletal muscle of the offspring. At day 180 to day 268 of gestation a total of 16 pregnant Brahman cows, were assigned into Control treatment (CON; n = 7), where cows were fed ad libitum a low crude protein basal diet plus mineral mixture; or Slow-released nitrogen (SRN, n = 9) based diet, where cows were fed a basal diet plus a slow-release nitrogen supplement. Muscle biopsy was performed at day 45 of age in calves and used to perform RNA sequencing (RNA-seq) and proteomic (HPLC-MS/MS) analyses. Although the experimental treatment did not show effects on transcript abundance, proteomic analysis revealed significant differences in protein expression. Enriched (adjusted p -value ≤ 0.05) biological processes from the exclusive proteins identified in calves’ skeletal muscle from SRN group are related to central energy metabolism (synthesis of Acetyl-CoA, tricarboxylic acid cycle, isocitrate metabolic process), regulation of calcium and nitrogen transport, and protein folding. Protein-protein interaction network assessed in the differentially abundant proteins (DAPs) revealed 4 main enriched biological processes, including ATP metabolic process, glucose metabolism, tricarboxylic acid cycle, and sarcomere organization. These findings suggest that maternal supplementation whit slow-release nitrogen during late gestation can positively influence postnatal energy metabolism in calf skeletal muscle.